Legal Actions and Consequences for Corporations Involved in Corruption - B, Yudiansyah; Zarzani, T. Riza (Proceedings of the International Conference on Multidisciplinary Science (INTISARI), 2024)
The purpose of writing this journal is to identify and analyze the methods and motives behind acts of corruption carried out by corporations, as well as to understand the organizational structure and market dynamics that influence these corrupt practices. And to evaluate the legal consequences that apply to corporations involved in acts of corruption and to examine the effectiveness of the application of these penalties in efforts to prevent and overcome corruption among corporations. The approach method used in this study is Normative Law (normative juridical) using a legislative approach, a conceptual approach, and a comparative and empirical approach (field data). The results of the study show that corporations are involved in acts of corruption through various methods that are often complex and covert, driven by motives to increase profits, dominate the market, or avoid regulation. The mechanisms they use range from bribery, tender manipulation, to money laundering practices. Corporations involved in acts of corruption can face a number of legal consequences, ranging from heavy fines, license revocation, asset confiscation, to operational restrictions. Although these penalties are intended to provide a deterrent effect, their effectiveness in preventing corporate corruption often varies. While fines may provide a financial impact, without significant internal changes in corporate culture and governance, the potential for corrupt practices to recur.